The development, standardisation and acceptability of the traditional Tsonga-Shangaan dishes, Xigugu and Xiendla hi vomu for use in ethnic restaurants - Viljoen, Annemarie T. (University of Pretoria, 2013)
Dissertation (MConsumer Science)--University of Pretoria, 2012.